Experience of Treatment of Aphthous Lesions of Oral Mucosa by Preparations on the Basis of Collagen and Digestase - Vladimirovich, Timoshin Anton (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Chronic recurrent aphthous stomatitis (CRAS) is a chronic disease which manifests itself on oral mucosa; its typical features are periodic remissions and exacerbations with appearance of aphthae. The WHO reports that this disease affects up to 20% population. Persons of both genders, who range in age from 20 to 60 years, suffer from this disease. CRAS is a great problem of modern dentistry because of constantly growing incidence rate. In the past years, the new complex preparations â€œFarmadontâ€ are synthesized on the basis of collagen and digestase. The objective of our research is to evaluate increase of effectiveness of the treatment of patients, who have CRAS, by the use of bioresorbable plates on the basis of collagen and digestase. Materials and Methods: We have conducted a clinical dental research which included examination and treatment of patients having the diagnosis â€œÐš12.0 CRAS.â€ Results and Conclusion: Results of photometry of lesion foci in the course of time revealed that the period of healing of aphthae was reduced in the main group, where plates â€œFarmadontâ€ were used, as compared with the control group.